EVALUACIÓN DE LA CALIDAD DEL AGUA DEL RÍO CUNAS MEDIANTE ÍNDICES FISICOQUÍMICOS Y BIOLÓGICOS, JUNÍN PERÚ - Custodio Villanueva, María (2015)
Objective: To evaluate the water quality of Cunas river by physiochemical and biological indices in order to identify the areas with good repair, between January and December 2013. Methods: It was used the observation, description and explanation methods; the non-experimental design of longitudinal type. Three sampling areas were defined: Angasmayo (Concepcion), Huarisca (Chupaca) and Pilcomayo (Huancayo). Water samples were collected in plastic bottles of two liters and sterile glass vials to determine the concentration of nitrates and phosphates, and thermotolerant coliforms, respectively. The parameters were measured in situ: dissolved oxygen (mg/l), total dissolved solids (mg/l), temperature (°C), pH and turbidity (FTU). These measurements were performed with portable equipments Hanna Instruments. Benthic macroinvertebrate samples were collected using a Surber net mesh aperture of 250 microns. Results:according to the INSF, Angasmayo provided good water quality (75,14 in rainy season; 74,23 in low water), Huarisca average quality (67,96 in rain; 65,22 low water) and Pilcomayo average quality (61,39 in rain; 55,82 in low water). According to the EPT index, Angasmayo showed good water quality, Pilcomayo average quality and Huarisca poor water quality. Conclusions:In Angasmayo the water bodies, both in the rainy and dry season, described as good quality water. In Huarisca as average or regulate water quality, and Pilcomayo as regular water quality (according INSF), and poor quality (according EPT).